Calcium oxalate crystals in leaves of Randia (Gardenieae, Rubiaceae): environmental response or diagnostic character? - Mayte Stefany Jiménez-Noriega; Alejandro De la Rosa-Tilapa; Alejandro Torres-Montúfar (Plant Ecology and Evolution)
Background and aims – Calcium oxalate crystals are the most common biominerals in plants and have a wide variety of forms, such as styloids, druses, raphides, prisms, and crystal sand. The shape, position, and number of crystals in plant tissues can have taxonomic value. For Rubiaceae, one of the most diverse angiosperm families, the presence of crystals may be taxonomically informative. In Mexico, one of the most diverse Rubiaceae genera is Randia, which occurs in arid, tropical, temperate, and coastal dune vegetation. The aim of this study is to explore the taxonomic value of calcium oxalate crystals in Randia. Furthermore, we aim to ascertain whether these crystals respond to the environmental conditions in which the plant grows. Material and methods – Ten Mexican Randia species were selected, three of which included individuals from different vegetation types. For each individual, three mature leaves obtained from herbarium samples from MEXU and FESC were selected for SEM processing and leaf clearing. Key results – Druses in the spongy parenchyma and palisade parenchyma were constant in all the species studied. The druses in the palisade parenchyma were always larger than those in the spongy parenchyma. In addition to druses in the intracellular parenchyma, R. tomatillo presented extracellular prisms in the epidermis as well as extracellular prisms and aggregate prisms in the mesophyll, which is a rare characteristic in Rubiaceae. Conclusion – The constant presence of druses in the mesophyll could serve as a possible characteristic to diagnose the genus Randia, whereas the variable presence of druse crystals in the epidermis and veins could be related to environmental factors. The prisms in R. tomatillo may be related to its occurrence in the harsh environment of coastal dunes.